Dose–Response Association of Metformin with Parkinson’s Disease Odds in Type 2 Diabetes Mellitus - Kuang-Hua Huang; Ya-Lan Chang; Shuo-Yan Gau; Tung-Han Tsai; Chien-Ying Lee (Pharmaceutics, 2022)
Background. Studies have demonstrated that patients with diabetes mellitus who receive metformin have a lower risk of developing Parkinson’s disease (PD). However, studies have also suggested that metformin may increase the risk of PD. In this study, we investigated whether metformin use was associated with the risk of PD in type 2 diabetes mellitus (T2DM). Methods. In this population-based cross-sectional study, patients with T2DM diagnosed between 2001 and 2018 were enrolled. We categorized these patients as metformin users or nonusers. Participants below 50 years old were excluded. Two models were employed to evaluate the associations of metformin exposure and use intensity with PD after 3 and 5 years of follow-up. Results. Patients with T2DM who received <300 cumulative defined daily doses (cDDD) of metformin and those with metformin use intensity of <10 DDD/month had respective odds ratios (ORs) for PD of 0.88 (95% confidence interval [CI] = 0.83–0.94) and 0.87 (95% CI = 0.81–0.93) in a 3-year follow-up. In a 5-year follow-up, such patients had respective ORs for PD of 0.94 (95% CI = 0.90–0.98) and 0.93 (95% CI = 0.89–0.98). Patients with T2DM who received ≥300 cDDD of metformin or used metformin with intensity of ≥10 DDD/month experienced no neuroprotective effects after 3 or 5 years. Conclusions. Metformin was associated with PD odds in T2DM in a dose–response association manner. Patients who received low dosage and intensity of metformin use were associated with lower odds of PD, while higher dosage and intensity of metformin use had no neuroprotective effect.